Husein Jafar Al-Hadar's Islam Mazhab Cinta: Meaning and Media Analysis of Instagram Content @husein_hadar - Norma Azmi Farida; Zainal Abidin (UIN Sunan Gunung Djati Bandung, 2024)
Instagram is a crowded arena with various information flows, from entertainment to religious content. In the religious context, narratives about da'wah in Indonesia have persuasive content, but some are provocative. Ideally, provocative narratives in social media preaching must be defeated by persuasive preaching. In this paper, there is a da'wah figure who moves the Islamic narrative of the school of love (Islam Mazhab Cinta), namely Husain Jafar Al-Hadar @husein_hadar. Specifically, this article highlights one of its contents on March 5, 2022, with the caption “Jika Kau Baca Buku, Pasti Kau Letakkan Senjata